PERBANDINGAN NILAI ISPU HARIAN DI 5 TITIK PEMANTAUAN UDARA DKI JAKARTA PADA SAAT LOCKDOWN MARET 2020 - Nelvidawati Nelvidawati; Angelalia Roza (Politeknik Negeri Jakarta, 2022)
One of the air quality conditions in the Special Capital City Region (DKI) Jakarta is the transportation sector. The air quality index is dominated by moderate conditions, even at dangerous levels. The COVID-19 pandemic caused the DKI Jakarta Provincial Government to lock down in March 2020. Research in several countries has shown that air quality has improved because people's mobility has been stopped. This study aims to determine the effect of the lockdown imposed in DKI Jakarta on its air quality and see a comparison at each point. The method used is descriptive method. The data analyzed in this study were collected from 5 points of the Air Quality Monitoring System (AQMS) monitoring tool. Based on the research, it was concluded that the lockdown imposed in DKI Jakarta only affected the location of point 1 at the Hotel Indonesia (HI) roundabout. The Air Pollution Status Index (ISPU) is dominated by good air quality conditions. Other areas such as West Jakarta, East Jakarta, North Jakarta and South Jakarta, the lockdown imposed in March 2020 did not have any effect on increasing the ISPU value. In 2021 the air quality condition in DKI Jakarta is worse than in previous years at all monitoring points since the activities have returned to normal and traffic jams frequently occur. Keywords: Air Quality Index, DKI Jakarta, Lockdown, Transportation.